2019
DOI: 10.1371/journal.pone.0222857
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran oil ameliorates inflammatory responses by enhancing mitochondrial respiration in murine macrophages

Abstract: Previous studies have revealed the anti-inflammatory properties of rice bran oil (RBO), but the detailed mechanisms are poorly understood. Recent studies on the molecular/cellular anti-inflammatory mechanisms of dietary components have demonstrated that mitochondrial respiration plays a key role in macrophage functioning. Since dietary lipids are major substrates for mitochondrial respiration through β-oxidation, the current study examined whether RBO regulates inflammatory responses by modulating mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Hence, the carnosine activity on NO, leading to increase nitrite, would not cause any adverse effect but might rather represent an additional positive pharmacological effect of this natural compound. Previous studies, using 500 ng/mL of LPS [66] or 1000 ng/mL LPS [67] to stimulate macrophages, showed significant changes in energy metabolism and mitochondrial functions. In the present study, using five and 10 times lower LPS concentrations than those used in the aforementioned studies, we found that 100 ng/mL LPS was sufficient to significantly perturb the energy and redox metabolism of macrophages (Figures 3 and 4), whilst being completely free of any cytotoxic effect.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, the carnosine activity on NO, leading to increase nitrite, would not cause any adverse effect but might rather represent an additional positive pharmacological effect of this natural compound. Previous studies, using 500 ng/mL of LPS [66] or 1000 ng/mL LPS [67] to stimulate macrophages, showed significant changes in energy metabolism and mitochondrial functions. In the present study, using five and 10 times lower LPS concentrations than those used in the aforementioned studies, we found that 100 ng/mL LPS was sufficient to significantly perturb the energy and redox metabolism of macrophages (Figures 3 and 4), whilst being completely free of any cytotoxic effect.…”
Section: Discussionmentioning
confidence: 95%
“…Regulation of chronic inflammation through switching the macrophage phenotype using dietary components is of growing interest. A prior study demonstrated that rice bran oil (RBO) had anti-inflammatory effects by regulating mitochondrial respiration of macrophages in a normal diet-fed mice model [ 27 ]. Therefore, in the current study, we evaluated the anti-inflammatory effects of rice bran oil in a high-fat diet-induced obese mouse model by performing in vivo and ex vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran oil has previously been shown to attenuate obesity, hyperlipidemia, and inflammation in mice and rats [ 25 , 26 , 44 ]. A previous study also demonstrated that RBO exerted its anti-inflammatory effects through modulating the mitochondrial respiration of macrophages in normal diet-fed mice [ 27 ]. In this regard, there is a lack of data regarding the effects of palm oil on local chronic inflammation and macrophage polarization in high-fat diet-induced obese mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations